(untitled) (International Bulletin of Applied Science and Technology, 2026)
This article analyzes the role of mobile learning in the modern education system from psychological and pedagogical perspectives. The impact of the educational process organized on the basis of mobile devices on students’ cognitive activity, motivation, independent learning skills and personal development is studied. It also highlights the issues of psychological and pedagogical factors, innovative methods, and the formation of digital competencies arising in the activities of teachers and students during the process of digital adaptation. The research results serve to develop practical recommendations for the effective implementation of mobile learning technologies into the educational process and ensuring adaptation to the digital environment.